Harmless women : a novel - Sharpe, Rebecca (Novelist) (Minotaur Books, 2026)
"Avalon Dale is a masterful grifter. She researches her victims thoroughly, kidnaps and sedates them, cleans out their bank accounts, and uses injections and hair clippers to change their appearance so that when they wake up, they can't easily prove who they are. For her last great score, Avalon's targeted Primrose Meath, and then she'll fade away to a life of ease and luxury--something she's dreamed of since a very tough childhood. On paper, Prim is the perfect target: wealthy, workaholic, and distracted by her cheating husband. But when Avalon finds Prim's husband dead, she can't escape so easily--not when she's been mistaken for Prim who's now wanted for murder. The two women--opposites, enemies--are suddenly on the run together, and must learn to get along, to depend on each other--in order to get away. And then, what starts as a cat-and-mouse run to the coast of England becomes a fight for their survival"-- Provided by publisher.